Proceedings of Tools for High Energy Physics and Cosmology — PoS(TOOLS2020) 2021
DOI: 10.22323/1.392.0001
|View full text |Cite
|
Sign up to set email alerts
|

Review on Dark Matter tools

Abstract: Whilst the need for dark matter was established almost a century ago, only its gravitational interaction has been confirmed so far, allowing for plethora of models for dark matter. The Weakly Interacting Massive Particles (WIMPs) category has received by far the biggest attention, however despite the enormous experimental efforts, these particles remain elusive. The attention of the community has hence moved on to investigate the dark matter landscape over a much larger number of models with varying degrees of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 100 publications
0
8
0
Order By: Relevance
“…is the thermally averaged annihilation cross section w.r. Eqs. (4)(5)(6) are widely used in relic density calculations, not the least because they take the same form even when including co-annihilations [16]. These equations have been implemented to a high numerical precision since the early versions of DarkSUSY, and we refer to Refs.…”
Section: Relic Density: Boltzmann Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…is the thermally averaged annihilation cross section w.r. Eqs. (4)(5)(6) are widely used in relic density calculations, not the least because they take the same form even when including co-annihilations [16]. These equations have been implemented to a high numerical precision since the early versions of DarkSUSY, and we refer to Refs.…”
Section: Relic Density: Boltzmann Equationsmentioning
confidence: 99%
“…Consequently, there is a huge demand on precision calculations both for the relic density and rates associated to other potentially observable DM signals. DarkSUSY [2,3] is one of the major public and generic codes to perform such calculations (complemented by MicrOMEGAs [4] and MadDM [5], which each have a somewhat different focus [6]).…”
Section: Introductionmentioning
confidence: 99%
“…The possible models that could lead to a stable particle are quite obvious in this parametrization and can be classified in two groups depending on whether the complex field S acquires a vacuum expectation value JHEP11(2021)202 (VEV) or not. In this work, we focus on the former case because it helps to avoid DD constraints [37][38][39][40][41]. Moreover it can also help to alleviate the instability problems of the scalar potential of the SM (see for instance ref.…”
Section: Jhep11(2021)202mentioning
confidence: 99%
“…A thorough review of many DM tools can be found in [26] The revolution in the field of BSM inference came with the advent of model-independent tools. The front-runner for SM fits is HEPFit [57], built upon a Bayesian Markov chain Monte Carlo, which includes a vast library of electroweak precision, Higgs and flavour observables, and can also work with BSM models [58,59].…”
Section: Inference and Samplingmentioning
confidence: 99%